2015
DOI: 10.1007/s11356-015-5573-5
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) at traffic and urban background sites of northern Greece: source apportionment of ambient PAH levels and PAH-induced lung cancer risk

Abstract: Thirteen particle-phase PAHs, including nine >4-ring congeners [Benz[a]anthracene (BaAn), Chrysene (Chry), Benzo[b]fluoranthene (BbF), Benzo[k]fluoranthene (BkF), Benzo[e]pyrene (BeP), Benzo[a]pyrene (BaP), Dibenzo[a,h]anthracene (dBaAn), Benzo[g,h,i]perylene (BghiPe), Indeno(1,2,3-c,d)pyrene (IP)], listed by IARC (International Agency for Research on Cancer) as class 1, class 2A, and 2B carcinogens, plus four ≤ 4-ring congeners [Phenanthrene (Ph), Anthracene (An), Fluoranthene (Fl), Pyrene (Py)], were concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
44
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 43 publications
11
44
4
6
Order By: Relevance
“…Compared with past data on these nine PAHs at KUWAMS, the concentration of total PAHs in the TSP observed in this study was lower than that observed from 2004 to 2014 (670 pg/m 3 in the cold period and 170 pg/m 3 in the warm period). In a general comparison with other background sites, the total PAH concentration at KUWAMS was within the ranges detected at urban background sites in Thessaloniki, Greece [34] (5.8 ± 8.4 and 5.9 ± 8.5 ng/m 3 for Σ13 PAHs bound to PM 10 and PM 2.5 , respectively); Dongying, China [35] (18.95 ± 16.51 ng/m 3 for Σ15 PAHs bound to PM 18 ); Gosan, Korea [36] (2.9 ng m −3 for 14 PAHs bound to PM 2.5 , detected in a study on gaseous and particulate PAHs at the Gosan background site in East Asia); and Virolahti, Finland [37] (4.07 ng/m 3 for 11 PAHs bound to PM 10 ). Table S1 presents the meteorological parameters at KUWAMS.…”
Section: Overviewsupporting
confidence: 64%
“…Compared with past data on these nine PAHs at KUWAMS, the concentration of total PAHs in the TSP observed in this study was lower than that observed from 2004 to 2014 (670 pg/m 3 in the cold period and 170 pg/m 3 in the warm period). In a general comparison with other background sites, the total PAH concentration at KUWAMS was within the ranges detected at urban background sites in Thessaloniki, Greece [34] (5.8 ± 8.4 and 5.9 ± 8.5 ng/m 3 for Σ13 PAHs bound to PM 10 and PM 2.5 , respectively); Dongying, China [35] (18.95 ± 16.51 ng/m 3 for Σ15 PAHs bound to PM 18 ); Gosan, Korea [36] (2.9 ng m −3 for 14 PAHs bound to PM 2.5 , detected in a study on gaseous and particulate PAHs at the Gosan background site in East Asia); and Virolahti, Finland [37] (4.07 ng/m 3 for 11 PAHs bound to PM 10 ). Table S1 presents the meteorological parameters at KUWAMS.…”
Section: Overviewsupporting
confidence: 64%
“…PAHs possess a potential health hazard because of their carcinogenic, mutagenic as well as teratogenic properties . Owing to their alarming abundance in the environment and adverse health effects, the US Environmental Protection Agency (EPA), the European Union (EU) and the International Agency for Research on Cancer (IARC) have promulgated several PAH compounds in their lists of priority pollutants in surface water for drinking purposes . For example, EPA′s maximum contaminant level (MCL) for PAHs in drinking water is 0.2 ppb.…”
Section: Methodsmentioning
confidence: 99%
“…[4,5] Owing to their alarming abundance in the environment and adverse health effects, the US Environmental Protection Agency( EPA), the European Union (EU) and the International Agencyf or Research on Cancer (IARC) have promulgated several PAHc ompounds in their listso fp riority pollutants in surface water ford rinking purposes. [6][7][8] For example, EPA'sm aximum contaminant level (MCL) for PAHs in drinking water is 0.2 ppb. Further,d ue to the high hydrophobicity of PAHs, their solubility in water is very low,a nd thus their determination in water samples becomes extremely challenging.…”
mentioning
confidence: 99%
“…Six main sources were established, including: oil and asphalt refineries, coal combustion, wood combustion, gasoline engine exhaust, diesel engine exhaust and oil spills. In the published paper, a chemical mass balance (CMB) model was established and source profiles were collected from the literature, effective and popular method to identify the origins of PAHs (US EPA, 2004; Kim et al, 2013;Manoli et al, 2016). Coal and wood combustion are the two major sources of PAHs in the Yellow river estuarine area, whose relative contribution were 30.5% and 27.7%.…”
mentioning
confidence: 99%